2021
DOI: 10.1021/acs.nanolett.1c03805
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Size Effect of Pt Ultrathin Nanowires on Oxygen Reduction Reaction

Abstract: The classical size effect of Pt particles on oxygen reduction reaction (ORR) suggests that the activity and durability would decrease with reducing the particle size, self-limiting the effectiveness in maximizing the Pt utilization efficiency with the particle-size-reduction strategy. Herein, we discover an anomalous size effect based on Pt nanowires (NWs) with tunable diameters, where the monotonically increasing activity and durability for ORR were observed with decreasing the diameter from 2.4 to 1.1 nm. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 44 publications
1
31
0
1
Order By: Relevance
“…Electrocatalytic energy conversion reactions such as oxygen reduction/evolution reactions (ORR/OER) are crucial in addressing the energy crisis. Catalysts can increase conversion efficiency and reaction selectivity by decreasing the overall reaction energy barrier and inhibiting possible side reactions. Although noble metal catalysts are often used due to their state-of-the-art catalytic activity, the exorbitant cost and rarity prevent their large-scale usage. Thus, it is significant to develop high-performance and low-cost non-noble metal-based electrocatalysts …”
Section: Introductionmentioning
confidence: 99%
“…Electrocatalytic energy conversion reactions such as oxygen reduction/evolution reactions (ORR/OER) are crucial in addressing the energy crisis. Catalysts can increase conversion efficiency and reaction selectivity by decreasing the overall reaction energy barrier and inhibiting possible side reactions. Although noble metal catalysts are often used due to their state-of-the-art catalytic activity, the exorbitant cost and rarity prevent their large-scale usage. Thus, it is significant to develop high-performance and low-cost non-noble metal-based electrocatalysts …”
Section: Introductionmentioning
confidence: 99%
“…The ultrathin thickness of the NW structure increases the exposure of catalytically Pt active sites to reaction molecules. In addition, low‐coordinated surface Pt atoms in Pt NWs can facilitate the adsorption and desorption of reagents and intermediates, and thus, the high atomic utilization by the atomic layer and low‐coordinated surface allows them to enhance catalytic activities 21,22 . For example, Lv et al reported that Pt–Pd NWs with a thickness of 3 nm exhibited larger catalytic activity than Pt and Pd nanoparticles toward HER 23 .…”
Section: Introductionmentioning
confidence: 99%
“…For heterogenous catalysis, it is well‐accepted that the atomic packing on exposure surface can directly affect the interaction between metal atoms and chemical species [4] . For example, unlike the closed packing in {111} facets, a more loose atomic packing, as well as the presence of a high density of under‐coordinated atoms, can enable the surface atoms stay in a weakly bonded environment and thus have a higher chemical activity to facilitate the absorption/desorption behavior [5] …”
Section: Introductionmentioning
confidence: 99%
“…[4] For example, unlike the closed packing in {111} facets, a more loose atomic packing, as well as the presence of a high density of undercoordinated atoms, can enable the surface atoms stay in a weakly bonded environment and thus have a higher chemical activity to facilitate the absorption/desorption behavior. [5] The shape evolution during nanocrystal growth is intrinsically governed by reducing the total surface energy of nanocrystal, and finally reaching the minimum value at a given condition. [6] Based on this, typical synthetic strategies on crystal facet engineering could be generally classified into two categories.…”
Section: Introductionmentioning
confidence: 99%